The Moderating Effect on an Internship Programme on the Relationship between Motivational Factors and Students` Carrier Decision in the Hospitality Industry in China - ZHANG, Hui; RASHID, Basri; MOHAMMED, Abdul Alem (Journal of Environmental Management and Tourism; Vol 7 No 4 (2016): JEMT Volume VII Issue 4(16) winter 2016DO - 10.14505//jemt.v7.4(16).15, 2017)
China is now enjoying fast growth of international tourism development, which contributes to creating a large amount of employment in the hospitality industry. Nevertheless, attracting and retaining talented students has become a significant problem in China due to a great proportion of HTM graduates fail to make their career decisions to work in the hospitality industry. It is therefore important to provide a value conceptual model that expounds on the theoretical relationships existing between motivational factors and students’ career decisions to enter the hospitality industry. This study contributes literature by clarifying the relationship between two motivational factors and students’ career decisions as well as by determining the moderating effect of an internship programme on such relationship.